Dynamics of the level of choreographic preparedness of athletes at the stage of preliminary basic training (on the basis of sports aerobics) - Тодорова, Валентина (Slobozhanskyi Herald of Science and Sport, 2017)
Valentina Todorova Purpose: to reveal the change in the level of choreographic preparedness of young athletes at the stage of preliminary basic training. Material & Methods: an expert evaluation of 61 athletes, gymnasts, sports aerobics. Following research methods were used: theoretical analysis of literary sources, method of expert evaluation, methods of mathematical statistics. Results: a methodology for assessing the choreographic preparedness of athletes at the stage of preliminary basic training was introduced. Based on the data obtained, it was found that in the group of gymnasts there was a significant increase in the choreographic skill, which was recorded according to the group indices of the formation of the choreographic preparedness, as well as all the criteria for choreographic readiness. Conclusion: experimentally proved the effectiveness of the introduction of the author's program of choreographic training in the training process of gymnasts at all stages of training athletes in order to improve their choreographic skills.